Feeder Pig Nursery Cost Return Projection - Dhuyvetter, Kevin C.; Tokach, Mike D.; Dritz, Steve S.; DeRouchey, Joel (My University, 2009)
This publication provides estimated cost and returns for a feeder pig nursery.
MF2151_2009_12
Keywords: MF2151; Livestock; Economics; MF